1983
DOI: 10.1099/00221287-129-3-865
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Responses to Antigens of Streptococcus mutans in Monkeys (Macaca fascicularis) Immunized against Dental Caries

Abstract: Immunization of rabbits or monkeys with walls prepared from Streptococcus mutans by a procedure including extraction with SDS at room-temperature induced antibodies to three antigens (A, B and C) detectable by crossed immunoelectrophoresis. Antigens A and B have previously been characterized as proteins of molecular weight 29 000 and 190 000, respectively. Antigen C was characterized as having a molecular weight of 70 000 and was purified by immunosorbent affinity chromatography and hydrophobic interaction chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 6 publications
2
27
0
Order By: Relevance
“…More recently, low molecular weight peptides have been generated from this antigen that confer protec tion without any possibility of side-effects [Lehner et al, 1985a]. Protection in primates varies with the immunogen, the route of immunization, and whether the animals have been exposed to fluoride, but reductions in caries have ranged from 50-60% [Lehner et al, 1981] to >90% [Lehn er et al, 1985a]; in one study, complete protection was achieved for 3 years [Russell et al, 1983]. There have been no clinical trials in humans of an anticaries vaccine.…”
Section: Vaccinationmentioning
confidence: 99%
“…More recently, low molecular weight peptides have been generated from this antigen that confer protec tion without any possibility of side-effects [Lehner et al, 1985a]. Protection in primates varies with the immunogen, the route of immunization, and whether the animals have been exposed to fluoride, but reductions in caries have ranged from 50-60% [Lehner et al, 1981] to >90% [Lehn er et al, 1985a]; in one study, complete protection was achieved for 3 years [Russell et al, 1983]. There have been no clinical trials in humans of an anticaries vaccine.…”
Section: Vaccinationmentioning
confidence: 99%
“…Two groups in England have independently demon strated the presence of specific proteins designated antigen I/II, I, II and III [Rus sell and Lehner, 1978;Russell et al, 1980a, b] and antigens A, B, C and D [Russell, 1979a;Russell et al, 1983] in cell extracts and culture supernatants of S. mutans se rotype c. Antigens I/II, I and B are high molecular weight proteins with antigen I/II existing as a combined form of anti gen I and II [Russell et al, 1980a], Other high mulecular weight proteins have later been identified and named IF [Hughes et al, 1980], PI [Forester et al, 1983] and SpaA [Holt et al, 1982], Antigen I/II seems to be identical with antigen B and PI [Forester et al, 1983] and with SpaA [Holt et al, 1982] and antigen B is iden tical with antigen IF [Russell, 1979a], Elec tron microscopic studies have recently shown that antigens I/II and III are pres ent on the outer surface of the cell wall structure [Moro and Russell, 1983] and these proteins can therefore be regarded as surface antigens. Protective immunity to dental caries has been demonstrated in monkeys immunized with antigens 1/11 and 1 [Lehner et al, 1980 and with antigens A and C .…”
Section: Candidate Antigensmentioning
confidence: 99%
“…Samples of the lysates were then examined for their antigen content by rocket immunoelectrophoresis using rabbit antisera specific for S . mutans wall-associated protein antigens A, B and C (Russell et al, 1983b), GTF and GBP (Russell, 1979a;Russell et al, 1983~). Four of the lysates gave precipitin peaks with the antiserum to GBP.…”
Section: R E S U L T Smentioning
confidence: 99%